Quantitative Estimation of Plumbagin in Various Parts of Plumbago rosea and Plumbago zeylanica - SHEEJA*, EDWIN; JOSHI, S.B.; JAIN, D.C. (Asian Journal of Chemistry, 2009)
In this work, the various parts of Plumbago rosea and Plumbago zeylanica have been standardized by estimating plumbagin. The dried plant materials were subjected to successive solvent extraction (petroleum ether (60-80 ºC), chloroform, acetone, ethanol and aqueous). The extracts that showed positive qualitative test were further taken for the estimation of plumbagin through HPTLC. The results indicated the concentration of plumbagin in the following manner, P. rosea root > P. zeylanica root > P. rosea stem > P. zeylanica stem> P. rosea leaf > P. zeylanica leaf.